Social media and community engagement's impact on student health and activity - Serikkhan Zhuzeyev; Nazym Tleuova; Ulyana Ivanova; Zalina Tazheva; Ilyos Abdullayev; Elena Koneeva; Irina Leontyeva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study presents one of the first attempts to systematically examine the influence of football media content and community on young students' healthy lifestyles and physical activity. Football media, as a unique phenomenon at the intersection of sports, entertainment, and social media, has significant, albeit ambiguous, potential to promote healthy lifestyles among young people.